2020
DOI: 10.1021/acs.inorgchem.0c00399
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Route to Heterometallic Group 4–Zinc Precursors for Binary Oxide Nanomaterials

Abstract: In this study, simple and efficient synthetic routes to a family of uncommon group 4−zinc heterometallic alkoxides were developed. Single-source molecular precursors with the structures [Cp 2 TiZn(μ,η-OR)(THF)Cl 2 ] (1), [Zr 3 Zn 7 (μ 3 -O)-(μ 3 ,η 2 -OR) 3 (μ-OH) 3 (μ,η 2 -OR) 6 (μ,η-OR) 6 Cl 6 ] (2), and [Hf 3 Zn 7 (μ 3 -O)(μ 3 ,η 2 -OR) 3 (μ-OH) 3 (μ,η 2 -OR) 6 (μ,η-OR) 6 Cl 6 ] (3) were prepared via reduction of Cp 2 TiCl 2 with metallic zinc or protonolysis of the metal−cyclopentadienyl bond in Cp 2 M′Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…About 20% of them feature zinc as a structural component (Banci et al, 2002;Andreini & Bertini, 2012). Zinc complexes exhibit a wide range of coordination numbers and coordination spheres, with tetrahedral (Ashurov et al, 2018;Petrus et al, 2020) and octahedral (Ashurov et al, 2011) environments being the most frequently observed.…”
Section: Chemical Contextmentioning
confidence: 99%
“…About 20% of them feature zinc as a structural component (Banci et al, 2002;Andreini & Bertini, 2012). Zinc complexes exhibit a wide range of coordination numbers and coordination spheres, with tetrahedral (Ashurov et al, 2018;Petrus et al, 2020) and octahedral (Ashurov et al, 2011) environments being the most frequently observed.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Hydrogen atoms and alkoxide ligands have been removed for clarity. Violet is nickel, green is titanium, red is oxygen, dark green is chloride, dark red is bromide, and grey is carbon with metallic Zn (1:2 Ti:Zn ratio) in a mixture of THF and 2-methoxyethanol at room temperature [90]. The two chloride ions from the titanocene dichloride complex were replaced by a chelating 2-methoxyethanol ligand using the excess Zn(OR) 2 to extract the chloride ions to form Zn(OR)Cl and/or ZnCl 2 [91].…”
Section: Coppermentioning
confidence: 99%
“…For example, decomposition of the cobalt-zirconium species CoZr 2 (acac) 2 (O i Pr) 8 under autogenic pressure resulted in the formation of spherical ZrO 2 and Co particles, covered in carbon . The thermal decomposition of the zinc-zirconium alkoxide Zr 3 Zn 7 O­(OH) 3 (OR) 15 Cl 6 has also been shown to result in the formation of ZrO 2 crystallites on the surface of ZnO nanowires . A further example is the SSP [Cu 4 Zr 2 O 2 (dmae) 4 (OAc) 8 ]·2H 2 O (dmae = N , N -dimethylaminoethanolato), which produced a CuZrO 3 -CuO composite using aerosol-assisted chemical vapor deposition .…”
Section: Introductionmentioning
confidence: 99%
“… 20 The thermal decomposition of the zinc-zirconium alkoxide Zr 3 Zn 7 O(OH) 3 (OR) 15 Cl 6 has also been shown to result in the formation of ZrO 2 crystallites on the surface of ZnO nanowires. 21 A further example is the SSP [Cu 4 Zr 2 O 2 (dmae) 4 (OAc) 8 ]·2H 2 O (dmae = N , N -dimethylaminoethanolato), which produced a CuZrO 3 -CuO composite using aerosol-assisted chemical vapor deposition. 22 There are potentially a number of advantages of including transition metals into the zirconia coatings for battery applications, including modifying the ionic conductor behavior of the film and increasing the stability of the protective layer, potentially via substitution of the transition metals into the surface and subsurface layers of the (active) electrode material.…”
Section: Introductionmentioning
confidence: 99%